The law and you: elections - Mokhtar, Khairil Azmin (Thomson Reuters (Sweet & Maxwell) Malaysia (Sdn Bhd), 2013)
This book is a collection of essays loosely based on the theme of elections. It is not meant to be a book describing all you need to know about elections, but addresses some topical issues that may be on the minds of the average person on the street relating to elections and what happens thereafter.